Effectiveness and safety of polatuzumab vedotin combined with zuberitamab plus cyclophosphamide, doxorubicin and prednisone in untreated diffuse large B-cell lymphoma: A real-world study from China - Wei Li; Lanfang Li; Xianming Liu; Zhao Peiqi; Zhengzi Qian; Lihua Qiu; Shiyong Zhou; Huilai Zhang (Blood, 2025)
Abstract Introduction Polatuzumab vedotin (pola) plus rituximab, cyclophosphamide, doxorubicin, and prednisone (R-CHP) demonstrated superior progression-free survival versus R-CHOP in untreated diffuse large B-cell lymphoma (DLBCL) with comparable safety. Recently, zuberitamab (Hi), a novel anti-CD20 monoclonal antibody with enhanced antibody-dependent cellular cytotoxicity, combined with CHOP, has shown non-inferior objective response rate (ORR) to R-CHOP in DLBCL and may offer higher complete response rates (CRR), especially in germinal center B-cell-like (GCB) DLBCL. Given the unmet clinical need in high-risk DLBCL and mechanistic synergy between antibody-drug conjugates (pola) and next-generation anti-CD20 agents (Hi), this study evaluated the real-world effectiveness and safety of Pola plus Hi-CHP (pola-Hi-CHP) in a Chinese cohort. Methods This retrospective study enrolled untreated adult DLBCL patients received pola-Hi-CHP at Tianjin Medical University Cancer Institute & Hospital in China between March 2024 and April 2025. Response was assessed by investigator using 2014 Lugano response criteria. Primary outcome was CRR at end of treatment (EOT), and secondary outcomes included ORR, and treatment-emergent adverse events (TEAEs). Subgroup analyses of CRR were performed based on age, Ann Arbor stage, B symptom, cell-of-origin, international prognostic index (IPI) score, expression of MYC and BCL2, and extranodal involvement. Results All patients completed the full six-cycle treatment regimen and received primary prophylaxis with long-acting granulocyte colony-stimulating factor (G-CSF). Among 72 evaluable patients (median age 63 years [range 19-83]), 54.2% were advanced stage. 16.7% patients presented with B symptoms, and 45.8% had elevated serum lactate dehydrogenase (LDH) level. 18.1% of patients had bone marrow involvement and 22.2% had more than one extranodal involvements. Most patients (76.4%) had an IPI score of 0-3, while 23.6% had an IPI score of 4-5. 54.2% of cases were non-germinal center B-cell-like (non-GCB) subtype, and 36.1% were GCB subtype. 33.3% of cases were MYC overexpression and 68.1%were BCL2 overexpression. 23.6% cases were double-expression of MYC and BCL2 proteins (DEL). Pola-Hi-CHP demonstrated a CRR of 83.3% (60/72; 95% confidence interval [CI] 69.7-89.8), with all patients attaining objective response (ORR 100%; 95% CI 95.0-100.0). Subgroup analyses demonstrated consistent CRR of pola-Hi-CHP across various subgroups, including those based on aged (<60 years: 85.2% [23/27] vs ≥60 years: 82.2% [37/45]), cell-of-origin (non-GCB: 87.2% [34/39] vs GCB: 84.6% [22/26]), and Ann Arbor stage (I/II: 81.8% [27/33] vs III/IV: 84.6% [33/39]). Patients with IPI 0-3 showed a CRR of 89.1% (49/55)compared with 64.7% (11/17) in patients with IPI 4-5, and those without B symptoms had a CRR of 85.0% (51/60) compared with 75.0% (9/12) in those with B symptoms. Bone marrow involvement was associated with a reduced CRR (76.9% [10/13] vs. 84.7% [50/59] in patients without involvement). Extranodal involvement also influenced outcomes. Among patients without extranodal involvement, the CRR was 85.7% (36/42), while it was slightly lower in those with at least one extranodal site involvement (80.0% [24/30]). Furthermore, patients with a single extranodal site involvement had a CRR of 85.7% (12/14), compared with 75.0% (12/16) in those with at least two sites involvement. Notably, patients with DEL achieved a CRR of 88.2% (15/17), while patients with MYC overexpression had a CRR of 87.5% (21/24) and patients with BCL2 overexpression had a CRR of 83.7% (41/49).The common grade ≥3 TEAEs included leukopenia (29.2%) and neutropenia (38.9%), with no new safety signals identified. Conclusions The pola-Hi-CHP regimen demonstrated encouraging effectiveness with CRR numerically exceeding historical R-CHOP and Pola-R-CHP benchmarks, particularly in non-GCB and DEL subgroups. The observed CRR reduction in high-risk IPI 4-5 patients underscores persistent therapeutic challenges in this population. Safety profiles aligned with established expectations for polatuzumab-based or zuberitamab-based regimens, with no new signals identified. These findings provide preliminary evidence supporting further evaluation of this novel combination in randomized controlled trials, particularly in subgroups defined by cell-of-origin and double-expression status.